The Effect of Different Guanidino Acetic Acid (GAA) Levels and Protein Source on Blood Profile of Tilapia Fish (Oreochromis niloticus) - Fakhirah Oktafiani Afifah; I Made Dedi Mahariawan; Wahyu Endra Kusuma; Bagus R. Hidayat; Ating Yuniarti2; Anik Martinah Hariati (Jurnal Penelitian Pendidikan IPA, 2025)
Tilapia (Oreochromis niloticus) is a freshwater fish that has high economic value and potential to be cultivated. The problem that often arises in tilapia cultivation is the lack of optimal use of the feed given. The purpose of this research was to find out blood profile of tilapia during culture period. The method used was a completely randomized design (CRD) with five treatments and every treatment with four replications. This study used 240 Tilapia with average weight of 15 g. The stocking density of the aquaria is 15 fish. Test feed in this study is the form of dry pellets consisting combination of GAA levels, protein content (25% dry matter bases), and source of protein (fish meal and non-fishmeal). During the cultured period of 70 days, fish fed by formula diet of 3% biomass per day. Sampling for blood profile tested of erythrocytes, leukocytes, and hematocrit is carried out after the research. The water quality of temperature, pH, and DO were daily monitoring. The combination treatment of guanidino acetic acid (GAA) levels with different protein sources (fishmeal and non-fishmeal) had a significant effect on total erythrocyte of tilapia, but did not have significant differences between treatments on total leukosyte and hematocrit. Treatment with 1.2 g/kg GAA, fish meal protein source was the best treatment in this research.